Diseño de una máquina trituradora de envases de vidrio (2018)
Initially the degree project as a search for information and background, through which it was possible to obtain a panorama about the current problems that originate around glass bottles. With the above, it was found that most of the problems caused by these elements can be reached through the recycling of them. Following the search for information, the requirement arises for a tool that in some way benefits the recycling process of glass bottles; In this way, the idea of designing a glass bottle grinding machine completes the grinding cycle, with a process of primary separation of materials outside the glass of the bottles. With clarity in the problem and the proposed solution, a search for information was achieved, through which the current technologies for the trituration of fragile materials are achieved. Knowing the above, a selection of alternatives has been made that adapt to the needs of the design of the machine and that sometimes adjust strictly with the initial design parameters.